PENGEMBANGAN OBJEK WISATA AIR PANAS HAPANASAN DI KABUPATEN ROKAN HULU - ", Ferawati; Yusrizal, Firdaus; Achnes, Sofia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this research is to know the development of tourism object AirPanas hapanasan kabupaten rokan hulu, especially in the development of is facility.Writer used Spillane theory (1994), which is said that facility is a supporting tool ofthe tourism object daily operational, to accommodate visitor need, indirectly supportgrowth but develop at the same time of after the attraction. Writer used ordinal scalefor measuring, which is likert scale, it is designet to ease respondent to answer somelevels in object which are going to measured.Visitor respondent about the development of the facili according to publicfacility, supporting and complementing tool in object ir panas hapanasan kabupatenrokan hulu. Writer found that visitor think that facilities are good enough,eventhough they need to be fixed in some aspect by improving and developingpromotion and marketing, and also fix the facilities in the location.Keywords : facilities, tourism, development, tourism objek.